Method for producing liquid crystal resin film

By employing specific bulk density pellets and controlled extrusion conditions, the method addresses particle generation and thickness fluctuations in liquid crystal resin films, achieving a more uniform film product.

JP7611693B2Active Publication Date: 2025-01-10POLYPLASTICS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020215497
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-01-10
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Conventional methods for manufacturing liquid crystal resin films using T-die or inflation methods result in the generation of particles and thickness fluctuations in the MD direction due to inadequate control of raw material properties and extrusion conditions.

Method used

The method involves using liquid crystal resin pellets with a specific bulk density and a single-screw extruder with adjusted screw compression ratio and L/D, along with controlled temperature settings to minimize lump formation and thickness variations.

Benefits of technology

This approach reduces the occurrence of lumps and thickness fluctuations in the MD direction, resulting in a more uniform liquid crystal resin film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611693000001
    Figure 0007611693000001
  • Figure 0007611693000002
    Figure 0007611693000002
  • Figure 0007611693000003
    Figure 0007611693000003
Patent Text Reader

Abstract

To provide a method for manufacturing a liquid crystalline resin film with reduced generation of blisters and thickness variation in the MD direction.SOLUTION: The method of producing a liquid crystalline resin film includes melting liquid crystalline resin pellets in a single-axis extruder, discharging the molten resin from the extruder to a die, extruding the molten resin from the die in sheet form, and cooling and solidifying it to produce the film, and the bulk density of the liquid crystalline resin pellets is 0.65 to 1.00 g / mL, the screw compression ratio of the extruder is 2.5 to 5.0, L / D is 18 to 45, and the melting point Tm (°C) of the liquid crystalline resin pellets and the die setting temperature Td (°C) satisfy Tm-10≤Td≤Tm+15.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a liquid crystalline resin film. [Background technology]

[0002] Liquid crystalline resins, such as liquid crystalline polyester resins, are widely used as high-performance engineering plastics because they have a good balance of excellent mechanical strength, heat resistance, chemical resistance, electrical properties, etc., and also have excellent dimensional stability. In addition, liquid crystalline resin films made of liquid crystalline resins are also produced by melt extrusion methods such as the T-die method and the inflation method (for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 05-043664 [Patent Document 2] Japanese Patent Application Publication No. 63-168327 Summary of the Invention [Problem to be solved by the invention]

[0004] According to the study by the present inventors, it was found that when a liquid crystalline resin film is produced by the T-die method or the inflation method, the use of conventional production methods tends to cause the generation of bumps (i.e., particles mixed in the liquid crystalline resin film) and the thickness tends to vary in the MD direction (i.e., the flow direction of the liquid crystalline resin film). The present invention has been made to solve the above problems, and an object of the present invention is to provide a method for producing a liquid crystalline resin film in which the generation of bumps and the thickness variation in the MD direction are reduced. [Means for solving the problem]

[0005] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that the above problems can be solved by using liquid crystalline resin pellets having a bulk density in a predetermined range as a raw material, and producing a liquid crystalline resin film using a single-screw extruder with a screw compression ratio and L / D adjusted to a predetermined range under conditions in which the melting point of the liquid crystalline resin pellets and the set temperature of the die satisfy predetermined ranges, and have completed the present invention. More specifically, the present invention provides the following.

[0006] (1) A method for producing a liquid crystalline resin film, comprising melting liquid crystalline resin pellets in a single screw extruder, discharging the molten resin from the extruder and feeding it to a die, extruding the molten resin from the die in a sheet form and cooling and solidifying it to produce a film, The bulk density of the liquid crystal resin pellets is 0.65 to 1.00 g / mL; The screw compression ratio of the extruder is 2.5 to 5.0, and the L / D is 18 to 45. A method for producing a liquid crystalline resin film, wherein the melting point Tm (° C.) of the liquid crystalline resin pellets and the set temperature Td (° C.) of the die satisfy Tm-10≦Td≦Tm+15.

[0007] (2) The liquid crystal resin pellets contain at least a structural unit derived from an aromatic hydroxycarboxylic acid, The Tm is 250° C. or higher. A method for producing the liquid crystalline resin film according to (1).

[0008] (3) the liquid crystalline resin pellets are cylindrical liquid crystalline resin pellets having a substantially cylindrical shape, The height of the cylindrical liquid crystal resin pellet is 2.0 to 4.5 mm. The diameter of the bottom circle of the cylindrical liquid crystal resin pellet is 1.5 to 3.0 mm. The screw groove depth in the feed section of the extruder is 1.1 times or more the height of the cylindrical liquid crystalline resin pellets. A method for producing a liquid crystalline resin film according to (1) or (2).

[0009] (4) The liquid crystalline resin pellets are spherical liquid crystalline resin pellets having a substantially spherical or substantially ellipsoidal spherical shape, The diameter of the spherical liquid crystalline resin pellets is 2.0 to 4.5 mm. The screw groove depth in the feed section of the extruder is 1.1 times or more the diameter of the spherical liquid crystalline resin pellets. A method for producing a liquid crystalline resin film according to (1) or (2). Effect of the Invention

[0010] According to the present invention, it is possible to provide a method for producing a liquid crystalline resin film in which the occurrence of bumps and thickness variation in the MD direction are reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0012] <Method of manufacturing liquid crystalline resin film> In the method for producing a liquid crystalline resin film according to the present invention, liquid crystalline resin pellets are melted in a single-screw extruder, the molten resin is discharged from the extruder and fed to a die, and the molten resin is extruded from the die into a sheet form and cooled and solidified to produce a film. The liquid crystalline resin melted in the extruder is discharged from the die into a sheet form, and is cast, for example, on a rotating cooling drum and rapidly cooled and solidified to obtain a liquid crystalline resin film. After cooling and solidifying, this liquid crystalline resin film may be subjected to longitudinal stretching and transverse stretching in that order as appropriate, and may finally be wound into a roll.

[0013] The extruder is a single-screw type extruder, and is provided with a single screw in a cylinder. The cylinder is provided with a supply port, and liquid crystal resin pellets are supplied into the cylinder through the supply port. The cylinder is composed of, in order from the supply port side, a supply section that transports a fixed amount of liquid crystal resin supplied from the supply port, a compression section that kneads and compresses the liquid crystal resin, and a transport and metering section that transports the kneaded and compressed liquid crystal resin to a discharge port while metering the discharge amount.

[0014] The screw compression ratio of the extruder is set to 2.5 to 5.0, and L / D is set to 18 to 45. Here, the screw compression ratio refers to the degree to which the liquid crystal resin is compressed in a molten state in order to knead it by applying back pressure, and is expressed as the volume ratio of the supply section to the conveying and measuring section (i.e., the volume per unit length of the supply section / the volume per unit length of the conveying and measuring section), and is calculated using the outer diameter d1 of the screw shaft of the supply section, the outer diameter d2 of the screw shaft of the conveying and measuring section, the groove diameter a1 of the supply section, and the groove diameter a2 of the conveying and measuring section. Also, L / D is the ratio of the cylinder length (L) to the cylinder inner diameter (D).

[0015] If the screw compression ratio is less than 2.5, the mixture is not sufficiently kneaded, unmelted portions are generated, the shear heat is small, and the melting of the crystals is insufficient, so that it is difficult to reduce the generation of bumps and / or the thickness variation in the MD direction. On the other hand, if the screw compression ratio is more than 5.0, the liquid crystal resin is deteriorated due to the heat generated by the excessive shear stress, or the liquid crystal resin molecules are easily cut and the molecular weight is reduced. This may cause the molten resin to become non-uniform, and the fluctuation in the discharge pressure of the extruder may become large. Therefore, in order to reduce the generation of bumps, reduce the fluctuation in the discharge pressure of the extruder, and reduce the thickness variation in the MD direction, the screw compression ratio is preferably in the range of 2.6 to 4.0, more preferably in the range of 2.7 to 3.5, and particularly preferably in the range of 2.8 to 3.0.

[0016] If L / D is less than 18, melting or kneading is insufficient, and fine crystals tend to remain as in the case of a small screw compression ratio, making it difficult to reduce the occurrence of bumps and / or thickness fluctuation in the MD direction. Conversely, if L / D is more than 45, the residence time of the liquid crystal resin in the extruder becomes too long, making the resin more likely to deteriorate. In addition, if the residence time becomes long, the liquid crystal resin molecules are likely to be cut and the molecular weight is likely to decrease. Therefore, in order to reduce the occurrence of bumps, reduce the discharge pressure fluctuation of the extruder, and reduce the thickness fluctuation in the MD direction, L / D is preferably in the range of 21 to 40, preferably in the range of 25 to 35, and particularly preferably in the range of 28 to 30.

[0017] The liquid crystalline resin is melted by the extruder configured as described above, and the molten resin is continuously sent from the discharge port to the die with a discharge pressure fluctuation of, for example, within 10%. Then, the molten resin sent to the die by the extruder is extruded from the die into a sheet shape, and is cast, for example, on a cooling drum and cooled and solidified to form a liquid crystalline resin film. Here, the melting point Tm (°C) of the liquid crystalline resin pellets and the set temperature Td (°C) of the die satisfy Tm - 10 ≤ Td ≤ Tm + 15. If Td < Tm - 10, the set temperature of the die is too low, and lumps are likely to occur, and the thickness variation in the MD direction is likely to increase. In some cases, holes may open in a part of the liquid crystalline resin film. On the other hand, if Td > Tm + 15, the set temperature of the die is too high, and the thickness variation in the MD direction is likely to increase. In some cases, holes may open in a part of the liquid crystalline resin film. Tm (°C) and Td (°C) preferably satisfy Tm - 9 ≤ Td ≤ Tm + 14, more preferably Tm - 8 ≤ Td ≤ Tm + 13.

[0018] [Liquid crystalline resin pellets] · (A) Liquid crystalline resin The liquid crystalline resin pellets contain (A) a liquid crystalline resin. The (A) liquid crystalline resin used in the present invention refers to a melt-processable polymer having the property of forming an optically anisotropic molten phase. The property of the anisotropic molten phase can be confirmed by a conventional polarization inspection method using crossed polarizers. More specifically, the confirmation of the anisotropic molten phase can be carried out by using a Leitz polarizing microscope and observing the molten sample placed on a Leitz hot stage at a magnification of 40 times under a nitrogen atmosphere. The liquid crystalline polymer applicable to the present invention shows optical anisotropy, that is, the polarized light usually passes through even in the molten stationary state when inspected between crossed polarizers.

[0019] The type of the liquid crystal resin (A) as described above is not particularly limited, and is preferably an aromatic polyester and / or an aromatic polyesteramide. Also, polyesters partially containing aromatic polyester and / or aromatic polyesteramide in the same molecular chain are included in the scope. As the liquid crystal resin (A), one having an inherent viscosity (IV) of preferably at least about 2.0 dl / g, more preferably 2.0 to 10.0 dl / g when dissolved in pentafluorophenol at a concentration of 0.1 mass% at 60°C is preferably used.

[0020] The liquid crystal resin (A) applicable to the present invention preferably contains at least a constituent unit derived from an aromatic hydroxycarboxylic acid, and is particularly preferably an aromatic polyester or aromatic polyesteramide containing at least a constituent unit derived from an aromatic hydroxycarboxylic acid.

[0021] More specifically, (1) Polyesters mainly composed of structural units derived from one or more aromatic hydroxycarboxylic acids and their derivatives; (2) polyesters consisting essentially of (a) structural units derived from one or more aromatic hydroxycarboxylic acids and their derivatives, and (b) structural units derived from one or more aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives; (3) A polyester mainly composed of (a) structural units derived from one or more aromatic hydroxycarboxylic acids and their derivatives, (b) structural units derived from one or more aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives, and (c) structural units derived from at least one or more aromatic diols, alicyclic diols, aliphatic diols, and their derivatives; (4) polyesteramides consisting essentially of (a) structural units derived from one or more aromatic hydroxycarboxylic acids and their derivatives, (b) structural units derived from one or more aromatic hydroxyamines, aromatic diamines, and their derivatives, and (c) structural units derived from one or more aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives; (5) polyesteramides mainly composed of (a) structural units derived from one or more aromatic hydroxycarboxylic acids and their derivatives, (b) structural units derived from one or more aromatic hydroxyamines, aromatic diamines, and their derivatives, (c) structural units derived from one or more aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives, and (d) structural units derived from at least one or more aromatic diols, alicyclic diols, aliphatic diols, and their derivatives. If necessary, a molecular weight modifier may be used in combination with the above structural components.

[0022] Preferred examples of specific compounds constituting the liquid crystal resin (A) applicable to the present invention include aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid (hereinafter also referred to as "HBA") and 6-hydroxy-2-naphthoic acid (hereinafter also referred to as "HNA"); aromatic diols such as 2,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (hereinafter also referred to as "BP"), hydroquinone, resorcin, a compound represented by the following general formula (I), and a compound represented by the following general formula (II); aromatic dicarboxylic acids such as terephthalic acid (hereinafter also referred to as "TA"), isophthalic acid, 4,4'-diphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and a compound represented by the following general formula (III); and aromatic amines such as 4-aminophenol and 1,4-phenylenediamine. [ka] (X is a group selected from alkylene (C1 to C4), alkylidene, -O-, -SO-, -SO2-, -S-, and -CO-) [ka] [ka] (Y:-(CH2) n -(n=1 to 4) and -O(CH2) n O-(n=1 to 4).

[0023] The liquid crystal resin (A) used in the present invention can be prepared by a known method using a direct polymerization method or an ester exchange method from the above-mentioned monomer compound (or a mixture of monomers). Usually, a melt polymerization method, a solution polymerization method, a slurry polymerization method, a solid-phase polymerization method, or a combination of two or more of these methods is used, and a melt polymerization method or a combination of a melt polymerization method and a solid-phase polymerization method is preferably used. The above-mentioned compounds having an ester forming ability may be used in the polymerization in their original form, or may be modified from a precursor to a derivative having an ester forming ability in a stage before polymerization. In these polymerizations, various catalysts can be used, and representative examples include metal salt catalysts such as potassium acetate, magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, antimony trioxide, and tris(2,4-pentanedionato)cobalt(III), and organic compound catalysts such as N-methylimidazole and 4-dimethylaminopyridine. The amount of the catalyst used is generally about 0.001 to 1 mass% relative to the total mass of the monomers, and particularly about 0.01 to 0.2 mass% is preferable. If necessary, the molecular weight of the polymer produced by these polymerization methods can be increased by a solid-phase polymerization method in which the polymer is heated under reduced pressure or in an inert gas.

[0024] The melt viscosity of the liquid crystal resin at the film-forming temperature and shear rate of 1000 / sec in the present invention is preferably 500 Pa·s or less, more preferably 50 to 400 Pa·s, and even more preferably 100 to 300 Pa·s. When the melt viscosity is within the above range, the liquid crystal resin itself or a composition containing the liquid crystal resin is likely to ensure film-forming properties during extrusion. In this specification, the melt viscosity is a value obtained by measurement in accordance with ISO11443.

[0025] Other Ingredients The liquid crystal resin pellets may consist of only the liquid crystal resin (A), or may contain other polymers, fillers (granular fillers, plate-like fillers, fibrous fillers, etc.), and other components such as stabilizers generally added to synthetic resins, such as antioxidants and ultraviolet absorbers, antistatic agents, flame retardants, colorants such as dyes and pigments, lubricants, crystallization accelerators, crystal nucleating agents, and release agents, as appropriate, depending on the required performance, within the range that does not impair the effects of the present invention. The other components may be used alone or in combination of two or more.

[0026] -Method for preparing liquid crystal resin pellets The liquid crystal resin pellets can be obtained, for example, by discharging the liquid crystal resin (A) prepared as described above from the bottom of a polymerization vessel and pelletizing the strands. When the liquid crystal resin pellets contain other components, the liquid crystal resin (A) and other components can be blended, melt-kneaded using a single-screw or twin-screw extruder, and then pelletized to obtain liquid crystal resin pellets.

[0027] ·Physical properties of liquid crystal resin pellets The bulk density of the liquid crystal resin pellets is 0.65 to 1.00 g / mL, preferably 0.68 to 0.95 g / mL, and more preferably 0.70 to 0.90 g / mL. If the bulk density is less than 0.65 g / mL, bumps are likely to occur and thickness variations in the MD direction are likely to increase. If the bulk density is more than 1.00 g / mL, the liquid crystal resin pellets become, for example, powder-like, so that the screw of the extruder is overloaded, and as a result, the film formability is likely to deteriorate. The bulk density of the liquid crystal resin pellets can be set to a desired value by, for example, appropriately adjusting the shape, dimensions, etc. of the liquid crystal resin pellets. In this specification, the bulk density of the liquid crystal resin pellets refers to the bulk density of the liquid crystal resin pellets measured after putting the liquid crystal resin pellets in a 50 mL measuring cylinder and vibrating the measuring cylinder so that the liquid crystal resin pellets are densely packed.

[0028] The melting point Tm of the liquid crystalline resin pellets is not particularly limited, and is preferably 250°C or higher, more preferably 260 to 370°C, and even more preferably 270 to 360°C, from the viewpoints of heat resistance, prevention of thermal degradation during melt processing of the liquid crystalline resin, and heating capacity of the extruder.

[0029] Shape of liquid crystal resin pellets The shape of the liquid crystal resin pellets is not particularly limited, and examples of the liquid crystal resin pellets include cylindrical liquid crystal resin pellets and spherical liquid crystal resin pellets. The cylindrical liquid crystal resin pellets refer to liquid crystal resin pellets that are approximately cylindrical. The term "approximately cylindrical" includes not only cylindrical shapes but also shapes that can approximate a cylinder (for example, a cylinder with uneven surfaces and a flattened elliptical cylinder). The spherical liquid crystal resin pellets refer to liquid crystal resin pellets that are approximately spherical or approximately ellipsoidal. The term "approximately spherical" means that the liquid crystal resin pellets are true spheres, but they do not have to be completely true spheres as long as they can approximate a true sphere (for example, a sphere with uneven surfaces). The term "approximately ellipsoidal" means that the liquid crystal resin pellets are not true spheres. In other words, the term "approximately ellipsoidal" includes all shapes that can approximate an ellipsoidal sphere (for example, an ellipsoidal sphere with uneven surfaces). Hereinafter, the liquid crystal resin pellets will be described separately for the case where the liquid crystal resin pellets are cylindrical liquid crystal resin pellets and the case where the liquid crystal resin pellets are spherical liquid crystal resin pellets.

[0030] When the liquid crystalline resin pellets are cylindrical, the height of the cylindrical liquid crystalline resin pellets is preferably 2.0 to 4.5 mm, the diameter of the circle at the bottom of the cylindrical liquid crystalline resin pellets is preferably 1.5 to 3.0 mm, and the screw groove depth in the supply section of the extruder is preferably 1.1 times or more the height of the cylindrical liquid crystalline resin pellets.

[0031] The height of the cylindrical liquid crystalline resin pellets is more preferably 2.5 to 4.2 mm, and even more preferably 3.0 to 4.0 mm, since this tends to further reduce the occurrence of bumps and thickness variations in the MD direction.

[0032] The diameter of the circle at the bottom of the cylindrical liquid crystalline resin pellet is more preferably 2.0 to 3.0 mm, and even more preferably 2.4 to 2.9 mm, since this tends to further reduce the occurrence of bumps and thickness variation in the MD direction.

[0033] Since the occurrence of bumps and thickness variations in the MD direction are more likely to be reduced, the screw groove depth in the supply section of the extruder is more preferably 1.2 to 2.0 times, and even more preferably 1.3 to 1.7 times, the height of the cylindrical liquid crystalline resin pellets.

[0034] When the liquid crystalline resin pellets are spherical liquid crystalline resin pellets having an approximately spherical or approximately ellipsoidal spherical shape, the diameter of the spherical liquid crystalline resin pellets is preferably 2.0 to 4.5 mm, and the screw groove depth in the supply section of the extruder is preferably 1.1 times or more the diameter of the spherical liquid crystalline resin pellets.

[0035] The diameter of the spherical liquid crystalline resin pellets is more preferably 3.0 to 4.3 mm, and even more preferably 4.0 to 4.2 mm, since this tends to further reduce the occurrence of bumps and thickness variations in the MD direction.

[0036] Since the occurrence of bumps and thickness variations in the MD direction are more likely to be reduced, the screw groove depth in the supply section of the extruder is more preferably 1.15 to 2.0 times, and even more preferably 1.2 to 1.3 times, the diameter of the spherical liquid crystalline resin pellets.

[0037] <Liquid crystal resin film> The liquid crystalline resin film obtained by the method for producing a liquid crystalline resin film according to the present invention is not particularly limited in its application, and can be used in various fields, for example, as an industrial film such as an insulating film, a waterproof film, or a heat-resistant film, or as a film for packaging materials such as a gas barrier film. EXAMPLES

[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0039] <Liquid crystal resin> Liquid crystal resin pellets 1A and 1A' After the following raw materials were charged into the polymerization vessel, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 1 hour. Thereafter, the temperature was further raised to 325°C over 3.5 hours, and then the pressure was reduced to 5 Torr (i.e. 667 Pa) over 20 minutes, and melt polymerization was carried out while distilling out acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel, pelletized by a strand cut method, and the cutter rotation speed was adjusted to obtain cylindrical liquid crystal resin pellets 1A with a height of 3.7 mm and a bottom circle diameter of 2.4 mm, or cylindrical liquid crystal resin pellets 1A' (for comparative examples) with a height of 5.1 mm and a bottom circle diameter of 3.5 mm. The melting point of the obtained pellets was 282°C. 4-Hydroxybenzoic acid (HBA); 1660g (73 mol%) 2-Hydroxy-6-naphthoic acid (HNA); 837 g (27 mol%) Metal catalyst (potassium acetate catalyst); 165mg Acylating agent (acetic anhydride); 1714g

[0040] Liquid crystal resin pellets 1B and 1B' After the following raw materials were charged in a polymerization vessel, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 1 hour. Thereafter, the temperature was further raised to 325°C over 3.5 hours, and then the pressure was reduced to 5 Torr (i.e. 667 Pa) over 20 minutes, and melt polymerization was carried out while distilling out acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel, pelletized by an underwater cut method, and the cutter rotation speed was adjusted to obtain spherical liquid crystal resin pellets 1B having a diameter of 4.1 mm, or spherical liquid crystal resin pellets 1B' having a diameter of 4.8 mm (for comparative examples). The melting point of the obtained pellets was 282°C. 4-Hydroxybenzoic acid (HBA); 1660g (73 mol%) 2-Hydroxy-6-naphthoic acid (HNA); 837 g (27 mol%) Metal catalyst (potassium acetate catalyst); 165mg Acylating agent (acetic anhydride); 1714g

[0041] Liquid crystal resin pellets 2 and 2' After the following raw materials were charged in a polymerization vessel, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 1 hour. Thereafter, the temperature was further raised to 330°C over 3.5 hours, and then the pressure was reduced to 10 Torr (i.e. 1330 Pa) over 15 minutes, and polycondensation was carried out while distilling out acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel, pelletized by a strand cut method, and the cutter rotation speed was adjusted to obtain cylindrical liquid crystal resin pellets 2 with a height of 3.4 mm and a bottom circle diameter of 2.9 mm, or cylindrical liquid crystal resin pellets 2' with a height of 4.5 mm and a bottom circle diameter of 3.5 mm (for comparative examples). The melting point of the obtained pellets was 323°C. 4-Hydroxybenzoic acid (HBA); 2524g (79.3 mol%) 2-Hydroxy-6-naphthoic acid (HNA); 867 g (20 mol%) Terephthalic acid (TA): 27 g (0.3 mol%) Metal catalyst (potassium acetate catalyst); 150mg Acylating agent (acetic anhydride); 2336g

[0042] Liquid crystal resin pellets 3S After the following raw materials were charged in a polymerization vessel, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 1 hour. Thereafter, the temperature was further raised to 360°C over 5.5 hours, and the pressure was reduced to 5 Torr (i.e., 667 Pa) over 30 minutes, and melt polymerization was carried out while distilling off acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel and pelletized by a strand cut method to obtain pellets. The obtained pellets were subjected to heat treatment (solid-phase polymerization) at 300°C for 8 hours under a nitrogen stream to obtain liquid crystal resin pellets 3S. The melting point of the obtained pellets was 353°C. 4-Hydroxybenzoic acid (HBA); 37g (2 mol%) 6-Hydroxy-2-naphthoic acid (HNA); 1218 g (48 mol%) Terephthalic acid: 560 g (TA); (25 mol%) 4,4'-dihydroxybiphenyl (BP); 628 g (25 mol%) Metal catalyst (potassium acetate catalyst); 165mg Acylating agent (acetic anhydride); 1432g

[0043] Liquid crystal resin pellets 3R and 3R' The liquid crystalline resin pellets 3S were fed into a twin-screw extruder (TEX-30α manufactured by Japan Steel Works, Ltd.) and melt-kneaded under conditions of a cylinder temperature of 370°C, a screw rotation speed of 250 rpm, and a discharge rate of 30 kg / h. The pellets were then quenched under conditions of a cooling water temperature of 45°C and a cooling time of 1 second, pelletized by a strand cut method, and re-pelletized. By adjusting the cutter rotation speed, cylindrical liquid crystalline resin pellets 3R with a height of 3.3 mm and a bottom circle diameter of 2.7 mm, or cylindrical liquid crystalline resin pellets 3R' with a height of 4.7 mm and a bottom circle diameter of 3.3 mm were obtained.

[0044] <Melting point> Using a differential scanning calorimeter (DSC, Hitachi High-Tech Science Co., Ltd.), the endothermic peak temperature (Tm1) observed when the obtained liquid crystal resin pellet was heated from room temperature at a temperature increase rate of 20°C / min was measured. Then, the temperature was kept at (Tm1+40)°C for 2 minutes. After cooling to room temperature at a temperature decrease rate of 20°C / min, the endothermic peak temperature (Tm2) observed when heating again at a temperature increase rate of 20°C / min was measured as the melting point.

[0045] <Melt viscosity> The melt viscosity of the liquid crystal resin was measured using a Capillograph 1B model manufactured by Toyo Seiki Seisakusho Co., Ltd. at the following temperature, using an orifice with an inner diameter of 1 mm and a length of 20 mm, at a shear rate of 1000 / sec in accordance with ISO11443. Liquid crystal resin pellets 1A, 1A', 1B, 1B': 280℃ Liquid crystal resin pellets 2, 2': 320℃ Liquid crystal resin pellets 3R, 3R': 350℃

[0046] <Bulk density> The obtained liquid crystal resin pellets were placed in a 50 mL measuring cylinder, and the measuring cylinder was vibrated so that the liquid crystal resin pellets were densely packed, and then the bulk density of the liquid crystal resin pellets was measured. The results are shown in Tables 1 to 3.

[0047] <Production of Liquid Crystalline Resin Film> The obtained liquid crystalline resin pellets were used as raw material and melted under the following conditions in a single screw extruder (20mmφ single screw extruder manufactured by Toyo Seiki Seisakusho Co., Ltd.) using a full-flight screw (screw diameter D: 19.8mm) with the screw compression ratio, L / D, and screw groove depth in the supply section of the extruder shown in Tables 1 to 3. The pellets were extruded into a film from a T-die (width: 150mm) at the tip of the extruder with the die temperature set as shown in Table 1, cooled, and the take-up speed was adjusted to produce a liquid crystalline resin film with a thickness of 100μm. Cylinder temperature: same as die temperature setting Screw rotation speed: 30 rpm Discharge amount: 1.6kg / h

[0048] <Thickness variation> The center part of the obtained liquid crystal resin film was observed by transmitted light, and the brightness information of the macro-photographed image was image-analyzed. Then, the thickness of the bright and dark parts in the MD direction was measured in total at 10 points with a constant pressure thickness measuring device manufactured by TECLOC Corporation. The measured thicknesses at 10 points were graphed, and the thickness variation was calculated as the ratio (%) of the difference between the maximum and minimum values ​​to the average thickness. The results are shown in Tables 1 to 3.

[0049] <Number of particles with a diameter of 50 μm or more> The liquid crystalline resin film was observed in a differential interference mode using an Olympus system microscope BX60, and the number of particles with a particle diameter of 50 μm or more in an area of ​​5 cm × 5 cm was counted. The results are shown in Tables 1 to 3.

[0050] [Table 1]

[0051] [Table 2]

[0052] [Table 3]

[0053] As is clear from the results shown in Tables 1 to 3, it was confirmed that the production methods of the examples could provide liquid crystalline resin films with reduced occurrence of bumps and reduced thickness variation in the MD direction.

Claims

1. A method for producing a liquid crystalline resin film, comprising: melting liquid crystalline resin pellets in a single-screw extruder; discharging the molten resin from the extruder to supply it to a die; extruding the molten resin from the die in a sheet shape and cooling and solidifying it to produce a film, The liquid crystalline resin pellets are (a) a polyester comprising structural units derived from one or more aromatic hydroxycarboxylic acids and their derivatives; (a) a polyester comprising structural units derived from one or more aromatic hydroxycarboxylic acids and their derivatives, and (b) structural units derived from one or more aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives; or A polyester comprising: (a) a structural unit derived from one or more aromatic hydroxycarboxylic acids and their derivatives; (b) a structural unit derived from one or more aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and their derivatives; and (c) a structural unit derived from at least one aromatic diol, alicyclic diol, aliphatic diol, and their derivatives. Contains The bulk density of the liquid crystalline resin pellets is 0.65 to 1.00 g / mL; The screw compression ratio of the extruder is 2.7 to 3.5, and the L / D is 25 to 35. A method for producing a liquid crystalline resin film, wherein the melting point Tm (° C.) of the liquid crystalline resin pellets and the set temperature Td (° C.) of the die satisfy Tm-10≦Td≦Tm+15.

2. The Tm is 250° C. or higher. A method for producing the liquid crystalline resin film according to claim 1.

3. The liquid crystalline resin pellets are cylindrical liquid crystalline resin pellets having a substantially cylindrical shape, The height of the cylindrical liquid crystal resin pellet is 2.0 to 4.5 mm. The diameter of the bottom circle of the cylindrical liquid crystal resin pellet is 1.5 to 3.0 mm. The screw groove depth in the feed section of the extruder is 1.1 times or more the height of the cylindrical liquid crystalline resin pellets. A method for producing the liquid crystalline resin film according to claim 1 or 2.

4. the liquid crystalline resin pellets are spherical liquid crystalline resin pellets having a substantially spherical or substantially ellipsoidal spherical shape, The diameter of the spherical liquid crystalline resin pellets is 2.0 to 4.5 mm. The screw groove depth in the feed section of the extruder is 1.1 times or more the diameter of the spherical liquid crystalline resin pellets. A method for producing the liquid crystalline resin film according to claim 1 or 2.

Citation Information

Patent Citations

  • Manufacture of liquid crystalline polyester sheet

    JP1988168327A

  • Polyester film and its production

    JP1993043664A

  • Production of liquid crystal resin composition pallet for molding

    JP1995118394A

  • Liquid crystal polymer pellets and production thereof

    JP1996192421A

  • Production of liquid-crystalline polyester film

    JP1996192463A